ASSESSMENT OF NUTRITIONAL ANAEMIA IN RELATION TO DIETARY INTAKE AMONG NEWLY DIAGNOSED BREAST CANCER WOMEN OF PATHAN ETHNICITY IN DISTRICT PESHAWAR (The Research of Medical Science Review, 2025)
Background: Cancer patients frequently have nutritional anaemia, especially iron deficiency anaemia, which can have a negative impact on their quality of life and treatment outcome. The most common cancer diagnosed in Pakistan and worldwide in females is breast cancer, whose management results are further complicated by delayed detection and restricted access to supportive care. Patients with breast cancer may have anemia for a variety of reasons, such as long-term inflammation, poor absorption, and a diet rich in iron, folate, and vitamin B12. Methodology: This cross-sectional study was conducted in the surgical B ward, Khyber Teaching Hospital, Peshawar. A sample of 110 newly diagnosed non-invasive breast cancer were selected randomly based on written consent patients, were investigated for the ABCD method of nutritional assessment. Data were collected using a self-constructed questionnaire. Demographic, anthropometric and biochemical parameters were recorded. Dietary intake was assessed using a 24-hour recall and compared with the RDA. Results: The results reveal that the majority of participants were from join family system, with a predominance of lower-income households. Non-menopausal women had a mean age (37.49 ± 7.19) years, while menopausal women had a mean age of 58.89 ± 7.101) years. The mean body mass index (BMI) of un menopause women (26.980 ± 4.1151), suggesting a higher prevalence of overweight and obesity. A mean BMI of (30.395 ± 5.5512) were found in menopausal women, which further supports the problem of overweight and obesity in this population. The mean random blood sugar level in non-menopausal women was (129.7313 ± 49.41831), whereas the mean for menopausal women was (154.4773 ± 34.91417). According to a complete blood count (CBC) study, menopausal women had a higher mean haemoglobin (HGB) level of (6.6030 ± .66900) than non-menopausal women, with the former having a mean HGB level of (9.4636± 1.70718), suggesting a large prevalence of anaemia. The C-Reactive protein, having mean and standard deviation of un menopause and menopausal women 5.34± 4.16), (5.4816 ± 2.28956) was found, which indicates a systematic pro-inflammatory state within the bodies of the patients. The dietary record showed the carbohydrates, which is recorded with a mean consumption of (292.2455 ± 103.92201), and this value is higher than the recommended amount of carbohydrates which is (225-325g/day), fats (103.09 ± 28.25), exceeding the RDA (45–75 g. Among water-soluble vitamins, B12, folic acid, and vitamin C were below or near requirements. Mineral analysis revealed insufficient calcium, zinc, iron and iodine intake. These findings suggest an imbalance in nutrient intake, with excessive fat and sugar consumption and deficiencies in several essential vitamins and minerals, potentially increasing the risk of non-communicable diseases such as breast cancer. Conclusion: Females of Pathan ethnicity who have recently been diagnosed with breast cancer in the Peshawar district have a high prevalence of nutritional anaemia, which is significantly correlated with low dietary iron intake. The necessity of early nutritional evaluation and dietary therapy in this susceptible group is highlighted by these findings.